Pengaruh Aksesibilitas dan Fasilitas Terhadap Word of Mouth Dengan Kepuasan Wisatawan Sebagai Variabel Mediasi dalam Perspektif Islam - Devi Ardiyani; Syamsul Hilal; Adib Fachri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Tourism destination management is currently required not only to provide adequate accessibility and facilities, but also to create tourist satisfaction in order to encourage positive word of mouth. In reality, many tourist destinations still face limitations in terms of access and facilities, which can affect tourist satisfaction and reduce their willingness to recommend the destination to others. In addition, studies that examine word of mouth from an Islamic perspective remain limited, particularly in the context of nature-based tourism. This study aims to analyze the effect of accessibility and facilities on word of mouth, with tourist satisfaction as a mediating variable, as well as the moderating role of Islamic perspective among visitors to Curup Gangsa Tourism Destination. This research employs a quantitative approach using a survey method, with data collected through questionnaires and analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM). The results indicate that accessibility and facilities have a positive and significant effect on word of mouth, both directly and indirectly through tourist satisfaction. Furthermore, the Islamic perspective is found to strengthen this relationship, suggesting that values such as honesty, justice, and convenience play an important role in shaping tourists’ recommendation behavior. These findings highlight the importance of integrating technical aspects of tourism destinations with Islamic values in tourism management.